Effect of slopes on rainfall interception by leaf litter under simulated rainfall conditions. Issue 8 (17th August 2022) - Zhao, Longshan; Meng, Ping; Zhang, Jinsong; Zhang, Jinxin; Sun, Shoujia; He, Chunxia
Abstract: Rainfall interception is one of the main hydrological functions of leaf litter. However, the effect of slope on the interception capacity of leaf litter has received little attention. The objectives of this study were to determine the capacities of leaf litters to intercept rainwater under different slopes (i.e., flat ground at 0° and inclined slopes at 5°, 15°, 25° and 35°) and to analyse the ways in which the slope affects the interception capacity of leaf litter. Under a simulated rainfall intensity of 50 mm/h, litter flows (i.e., infiltration flow, slope flow and lateral flow) through three types of leaf litter (i.e., Pinus massoniana needleleaves and Osmanthus fragrans and Magnolia grandiflora broadleaves) were measured. The leaf litter biomass per unit area was 0.5 kg/m 2 in the experimental box, and the interception capacity was calculated using the difference between rainfall and litter flow. The results show that the interception capacity of broadleaves was greater than that of needleleaves. The effect of slope was more pronounced than that of leaf shape because the rainwater stored on the leaf surfaces contributed to the generation of litter flow as the slope increased. The rainfall amount intercepted by each leaf litter decreased with increasing slope, and changes in the proportion of rainfall interception by leaf litter with increasing rainfall duration can be described by an exponential function ( R 2 > 0.80, p < 0.001). The maximum dynamic interception capacity ( C max ) and effective interception capacity ( C min ) of the three leaf litter types decreased as the slope increased. Statistical analyses show that 15° is a critical slope threshold that influences rainfall interception by leaf litter and litter flow. When the slope was greater than 15°, leaf litter interception capacities significantly decreased and the level of litter flow significantly increased. Therefore, slope affects the interception capacity of leaf litter and this impact should be considered in the estimation of litter interception storage on an inclined slope. Abstract : The infiltration flow, slope flow and lateral flow through litter were measured. The leaf litter interception capacity of broadleaves is greater than that of needleleaves. The 15° is a critical slope affecting the leaf litter interception capacity.